Kerbau dalam Tradisi Megalitik Etnis Batak di Sumatera Utara - Nenggih Susilowati (Berkala Arkeologi Sangkhakala, 2007)
AbstractBuffalo was an important animal for people with their megalithic tradition living until now. They have been used it, showed by discovering buffalo ornament in megalithic sites. How useful this animal have been made it as an sacred ornament or profane in some traditional houses.